ANALISIS GAYA BAHASA DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI - Moch. Arif Bina Mandra (JURNAL ILMIAH BAHASA DAN SASTRA, 2018)
Figurative language is a way to express ideas in written and oral production by involving feelings and soul. The present study focuses on describing (1) figurative language used by Ahmad Tohari in the novel Orang – Orang Proyek, (2) the most frequently used figurative language, and (3) the reasons of the use of figurative language in the novel. The design of the study was descriptive qualitative by employing content analysis method. The source of the data was the novel Orang – Orang Proyek. Fields notes were administered to collect the data including reducing data, coding the data as well as classifying the data. The research findings show that the kinds of figurative language used were (a) comparison, (b) contrast, (c) bond , and (d) repetition. Besides, Hyperbola was the most frequently used in the novel because Ahmad Tohari intended to convey moral values by presenting the story inside the novel, so it motivated people to give respects to the poor. Keywords: Figurative language, novel, Orang-Orang Proyek